Wave attenuation study on a wide-band seismic metasurface using capped pillars - Hajjaj, Muhammad Masaud; Tu, Jianwei (Comptes Rendus. Mécanique, 2022)
We present the results of a numerical study on a seismic metasurface that achieves wide bandgap for low frequencies and with relatively smaller resonators. The metasurface consists of periodic concrete pillars with rigid caps supported on rubber between the caps and pillars and placed above ground. The study shows that such a metasurface creates a barrier against elastic waves having frequencies in the seismic frequency range. The results are further validated by a frequency-domain and time-transient study. The proposed metasurface configuration is simple and can be realized with readily available materials.